FAKTOR PEMBERIAN ASI EKSKLUSIF PADA BAYI BERDASARKAN TEORI PERILAKU WHO - Ema Kahrismawati; Esti Yunitasari; Retnayu Pradanie (Pediomaternal Nursing Journal, 2014)
Breastfeeding contains nutrients for optimal growth and development on infants. WHO (World Health Organization) andthe government recommend exclusive breastfeeding, however the mother's behavior in exclusive breastfeeding is stilllow. According to the WHO Behavioral Theory, exclusive breastfeeding is one of health behaviour that influenced manyfactors. The purpose of this study is to analyze the factors of exclusive breastfeeding on infants based on WHObehavioral theory. The design of the study was descriptive analytic with cross-sectional approach. The population wasmothers with the infants of 6-12 months. The 32 sample respondents were chosen by purposive sampling technique. Theindependent variables in this study were knowledge, attitude, personal reference, resources, and culture. The dependentvariable was exclusive breastfeeding. The data were collected by using questionnaire and analyzed by using chi squaretest with a degree of significance α < 0.05. The results showed a significant correlation between knowledge factor(p = 0.007), attitude factor (p = 0.005), personal reference factor (p = 0.011), resource factor (0.004), and cultural factor (p= 0.004) with exclusive breastfeeding. The factors in WHO behavioral theory (knowledge, attitudes, personal reference,resources, and culture) have a significant correlation with exclusive breastfeeding. Further research was suggested toenhance and support exclusive breastfeeding with an effective health education.